A TTE-LAN Communication Scheme for Tunnel Rescuing. Issue 5 (June 2019) - Su, Zhong; Chen, Jinhui; Xu, Zhan; Liu, Ning; Li, Ling
Abstract: In this paper, a communication scheme for tunnel rescuing is proposed, in which a moving base station (BS) is used for communication -devices in an isolated space and the ones in the outer space after tunnel collapse. Local area network (LAN) links are used for the direct communication between the base station and the inner terminals while an electrode based through-the-earth (TTE) communication link is used for the direct communication between the BS and the outer terminals. It enables the portability of the terminal devices for construction workers and ensures the communication reliability after tunnel collapse. The performance advantage of the proposed rescue communication system is demonstrated by simulation results.